"CREATIVE ETHNOMUSICOLOGY” AND AFRICAN ART MUSIC: A CLOSE MUSICAL READING OF WOOD AND CLAY, KUNDI DREAMS AND UMRHUBHE GEESTE BY ANTHONY CAPLAN - Brukman, Jeffrey (International Library of African Music, 2017)
This article deals with Anthony Caplan's application of African art music through the lens of three works whose instrumentation and compositional processes result in pieces that transcend conventional boundaries. These works emerge as integrated artistic products exceeding the limitations of conventional musical expression. Through close musical readings of Wood and Clay, Kundi Dreams and Umrhubhe Geeste, Caplan's employment of "creative ethnomusicology” (term first used by Akin Euba) becomes evident as his knowledge, experience and familiarity with a wide range of musical styles and cultures coalesce in the creation of original works of musical art. Combining either the udu, Kundi harp or umrhubhe with the oboe Caplan's compositional amalgam merges sonic qualities from African and Western musical domains, including aspects of Eastern musicmaking. Evincing the attributes of African art music-labelled by Euba as African-European art music-Caplan's three works represent a growing body of repertoire from South Africa (a relative latecomer to this style of writing) embodying the essence of African art music.
Keywords: Polyrhythm; Musical instruments; Umrhubhe (Instrument); African Pianism; Hemiola; Kundi Harp (Instrument); Udu (Instrument); African Music